2021
DOI: 10.1186/s12888-021-03527-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-traumatic stress disorders and associated factors one month after the outbreak of the COVID-19 among the public in southwestern China: a cross-sectional study

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic has rapidly spread across the whole world and brought strong psychological impact. This study aimed to evaluate the prevalence of post-traumatic stress disorders (PTSD) in the general people of southwestern China and associated factors 1 month after the outbreak of the COVID-19. Methods This study was started on 4–10 Feb 2020 based on online survey. The present work was carried out in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…We also found that a younger age was associated with PTSD. This association was not found to be statistically significant in the previous study of the Norwegian general population [ 20 ], whereas it has been significantly associated with PTSD in several studies investigating post-traumatic stress reactions in the population during the early stage of the COVID-19 outbreak [ 37 , 38 , 39 ]. Thus, sociodemographic covariates to PTSD among people with a visual impairment appear to largely mirror those found in the general population.…”
Section: Discussionmentioning
confidence: 66%
“…We also found that a younger age was associated with PTSD. This association was not found to be statistically significant in the previous study of the Norwegian general population [ 20 ], whereas it has been significantly associated with PTSD in several studies investigating post-traumatic stress reactions in the population during the early stage of the COVID-19 outbreak [ 37 , 38 , 39 ]. Thus, sociodemographic covariates to PTSD among people with a visual impairment appear to largely mirror those found in the general population.…”
Section: Discussionmentioning
confidence: 66%
“…The analysis conducted indicates that there is no relation between the symptoms of posttraumatic stress and the age and job seniority of those analysed. In the context of the "age" variable, the findings are ambiguoussome confirm the greater risk of PTSD amongst younger people (Lei et al, 2021;Pasha et al, 2023), while others indicate a lack of such a relation (Roel, Lara, Bilsen, 2021). In the analysed group, there were no younger employees than 28 year olds (and the average age of those analysed was 33.98 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing the quality of life and impairing work performance, post-traumatic stress disorder can also lead to a significant medical and economic burden and increase the risk of suicide. If left uncontrolled, PTSD can cause permanent damage, including intrusion, avoidance, irritability, and emotional numbness for patients (9).…”
Section: Introductionmentioning
confidence: 99%